Pelatihan Penguasaan Kosakata Bahasa Inggris Menggunakan Metode TPR Bagi Anak-Anak Panti Asuhan Al Mim Palangka Raya - Nurliana (Jurnal Pengabdian kepada Masyarakat Radisi, 2023)
Mastery of English vocabulary is not easy, considering that English is a foreign language. To master English vocabulary, the appropriate learning method is needed. That is the basis for carrying out the training of English vocabulary mastery using Total Physical Response (TPR) method for the children of Al Mim Palangka Raya Orphanage. This training activity was attended by 10 training participants and accompanied by one instructor. This activity was carried out in June year 2022 for one day which included preparation, implementation, and evaluation. The training material was in the form of English vocabulary mastery using the Total Physical Response (TPR) method. The English vocabulary list given was related to the parts of body and face. The results of the training showed that Total Physical Response (TPR) method could be applied well in mastering English vocabulary. This method could make the training participants very enthusiastic, it was helpful for the training participants, and the vocabulary learning atmosphere became fun, so that the English vocabulary material provided could be easily understood by all participants of the training.